Analyzing Revitalization of Multicultural Education on Higher Education to Reduce Negative Stereotypes in Indonesia - FatmaWati FatmaWati; Nurul Azmy Rustan; Gustia Haryati (Qubahan Academic Journal)
A negative stereotypes are the root of big problems in this country. It is the forerunner to the birth of hatred and racist behavior. The negative stereotypes must be reduced. One way that can be done is by revitalizing multicultural education as an educational concept that is most friendly to diversity. This study aims to describe the revitalization of multicultural education in tertiary institutions to reduce negative stereotypes. This study uses a qualitative method with a concept analysis approach. Data collection techniques using document studies. The revitalization of multicultural education is carried out by reviewing the focus, goals, values, and approach of multicultural education. There are four approaches to multicultural education, namely the transformation, additive, contribution, and social action approaches. This revitalization is carried out so that the implementation of multicultural education in tertiary institutions as a macro environment can be carried out properly. The impact is the reduction of negative stereotypes so that social conflicts can be prevented.